Values and Behaviour: The Literary Concept of “Bosom” in the Akan Culture - Peter Arthur (Noyam Publishers, 2021)
This paper sees the Akan concept of “bosom”, translated into English as “lesser god”, as a very powerful socializing instrument used in constructing social order in the community. The aim of this paper is not to discount or dismiss the spiritual powers of the “bosom” but to use oral literature as a platform to investigate the role of the Akan people in the construction of what is known as “bosom”. This study has recourse to qualitative research methods in gathering data, the researcher immersing in the culture through formal and informal interviews and participant observation. The study also goes further to use the literary stylistics approach in analyzing the data. The findings are that man makes the taboos and the lesser gods execute the punishment. Again, taboos are values which constitute the tracks on which the society moves. These values “disguised” as “bosom” work, thanks to the fear factor in the Akan concept of “bosom”, making Akans literally worship these values in the form of “bosom”.